2012
DOI: 10.5296/ijld.v2i3.1775
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Computer Based Testing Method for the Conduct of Examinations at the University of Ilorin

Abstract: This paper presents an overview of the application of Information and Communication Technology in the conduct of post-UTME and other examinations at the University of Ilorin. It provides a brief historical background to the practice at the University, dating back to 2005 when it started by adopting the Pen-and-Paper Testing up to the present practice, using the Computer-Based Testing method. The paper underscored the challenges associated with the former practice, thus justifying the introduction of the latter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 7 publications
1
14
1
Order By: Relevance
“…This tends to fall in line with the global recognition of e-exams as a means of providing credibility and civility to examination system, thus improving the education sector (Akpata, 2013). This also tallies with the finding of Alabi, Issa and Oyekunle (2012) that undergraduates at the University of Ilorin preferred computer-based testing to pencil-and-paper examination.…”
Section: Discussionmentioning
confidence: 93%
“…This tends to fall in line with the global recognition of e-exams as a means of providing credibility and civility to examination system, thus improving the education sector (Akpata, 2013). This also tallies with the finding of Alabi, Issa and Oyekunle (2012) that undergraduates at the University of Ilorin preferred computer-based testing to pencil-and-paper examination.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have indicated that technology-based testing in K-12 settings brings potential benefits as mentioned above (Alabi, Issa, & Oyekunle, 2012;Luecht & Sireci, 2011;Friedrich, 2008;Way, Davis, & Fitzpatrick, 2006;Chapelle, 2003). Moreover, as the data from previous surveys signpost students' positive responses towards this kind of test (Way, Davis, & Fitzpatrick, 2006), the present study aims at exploring whether those affirmative reactions also occur in the Indonesian context, particularly to elementary school students.…”
Section: Doimentioning
confidence: 98%
“…As a viable alternative to paperand-pencil testing, a technology-based test has been a broad-based production that encompasses a large variety of assessment types, purposes, test delivery designs, and item types appropriated for wide-ranging areas that cover educational accountability and achievement testing, college and graduate admission testing, professional certification and licensure testing, psychological testing, intelligence testing, language testing, employment testing, adult education, and military use (Luecht & Sireci, (2011). Friedrich (2008) and Alabi, Issa, & Oyekunle (2012) support by stating that these types of testing allow the users to write, organize, deliver, and report on tests or surveys. Besides providing results more quickly than the paper-based testing, computer-based testing or web-based testing enable someone who has minimal or no previous computer experience to take the test as it commonly provides instruction tutorials before the examination begins.…”
Section: Doimentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005 the university system in Nigeria launched what they term post JAMB screening examination as a means of authenticating or validating scores obtained from JAMB. In response to some challenges faced in assessing candidates through the paper and pencil test, the university of Ilorin through her Senate became one of the first universities in Nigeria to commence the Computer Based Test for applicants in the year 2008 (Alabi, Issa, and Oyekunle, 2012). Similarly, Nnamdi Azikiwe University which is a federal university in Nigeria was said to have started computer based examination in 2015 as reported by Nnamdi Azikiwe University (nd).…”
Section: Introductionmentioning
confidence: 99%